2004
DOI: 10.1002/ijc.20411
|View full text |Cite
|
Sign up to set email alerts
|

Coamplification and coexpression of GRB7 and ERBB2 is found in high grade intraepithelial neoplasia and in invasive Barrett's carcinoma

Abstract: The human growth factor receptor-bound protein 7 gene (GRB7), the founding member of a family of adaptor molecules has been shown to regulate cell migration and has been implicated in tumor progression. GRB7 is localized in close proximity to the ERBB2 gene within an amplicon previously identified in Barrett's adenocarcinoma (BCA). We evaluated gene amplification and mRNA expression of GRB7 and ERBB2 in Barrett's carcinoma and its associated precursor lesions to assess their possible role in Barrett's malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
0
35
1
Order By: Relevance
“…13 Others report similar rates of ErbB2 positivity in oesophageal adenocarcinomas, highlighting the impact of ErbB2 amplification and ERBB2 overexpression during the malignant progression of Barrett's metaplasia to invasive cancer. [27][28][29] The relatively high number of ErbB2-positive cases in our study compared with other reports may be due to the definition of ErbB2 positivity, which was based on the guidelines of the ToGA study and the EMEA for trastuzumab (Herceptin r ) treatment for advanced gastric cancer. This recommendation requires a ErbB2 score of 3 þ by immunohistochemistry or an amplification level of Z2 (ErbB2/Chr17) even in small tumour cell clusters, 10 which is different from the breast carcinoma requirements, in which cases with a ErbB2/ Chr17 ratio between 1.8 and 2.2 are considered as equivocal and ErbB2 expression is less heterogeneous.…”
Section: Discussionmentioning
confidence: 71%
“…13 Others report similar rates of ErbB2 positivity in oesophageal adenocarcinomas, highlighting the impact of ErbB2 amplification and ERBB2 overexpression during the malignant progression of Barrett's metaplasia to invasive cancer. [27][28][29] The relatively high number of ErbB2-positive cases in our study compared with other reports may be due to the definition of ErbB2 positivity, which was based on the guidelines of the ToGA study and the EMEA for trastuzumab (Herceptin r ) treatment for advanced gastric cancer. This recommendation requires a ErbB2 score of 3 þ by immunohistochemistry or an amplification level of Z2 (ErbB2/Chr17) even in small tumour cell clusters, 10 which is different from the breast carcinoma requirements, in which cases with a ErbB2/ Chr17 ratio between 1.8 and 2.2 are considered as equivocal and ErbB2 expression is less heterogeneous.…”
Section: Discussionmentioning
confidence: 71%
“…The reasons for these contradictory results need to be addressed in future studies. It has been proposed that coexpression of the adaptor protein Grb7 and HER-2 may contribute to an invasive tumor phenotype [37,67], consistent with a role for Grb7 in cell migration.…”
Section: The Role Of Her-2 In Esophageal Cancermentioning
confidence: 87%
“…We recently showed that PPP1R1B/DARPP-32 is a novel cancer gene with a potent antiapoptotic potential that may contribute to the drug resistance and poor outcome phenotype in UGCs (37). Amplification and expression of ERBB2 and GRB7 was recently reported in Barrett's adenocarcinoma (38)(39)(40). However, these studies lacked data related to the expression of other genes that are between or at the boundaries of ERBB2 and GRB7.…”
Section: Discussionmentioning
confidence: 99%